Pelacakan Virus Bovine Viral Diarrhea pada Darah yang Dikoleksi dengan Kertas Saring Flinders Technology AssociatesTM (DETECTION OF BOVINE VIRAL DIARRHEA VIRUS FROM BLOOD SAMPLES COLLECTED USING FLINDERS TECHNOLOGY ASSOCIATESTM CARDS) - Wuryastuti, Hastari; Wasito, Raden; Putro, Prabowo Purwono (Jurnal Veteriner, 2016)
Bovine viral diarrhea virus (BVDV) is a common pathogen that causes major economic losses to dairyindustry worldwide. Amplification of 5’-UTR regions of BVDV genome from blood samples usingreversetranscriptase polymerase chain reaction (RT-PCR) is one of sensitive and accurate techniques forBVDV detection. A common limitation for molecular detection of virus is the ability to obtain high qualityof nucleic acid in the samples. Inappropriate storage conditions will result in a false negative test. FiveEDTA-blood samples collected from BVDV persistently infected cattle were used in the present study.Ten repetitions were done for each sample. The blood were then dripped in the middle part of the FlindersTechnology AssociatesTM (FTA) cards and let it dried for approximately 2 hours. The effectiveness of theFTATMcards for storage and retrieval of BVDV RNA from blood samples molecularly using RT-PCRtechnique were tested and evaluated. The results proved that FTATM cards are effective and safe for thestorage of BVDV genome for a long period at room temperature. Based on the result of the present study,it can be concluded that in veterinary medicine field, the application of FTATM technology needs to bedeveloped to various type of samples and should be used routinely for collecting samples containinginfectious agents.
Keywords: Bovine viral diarrhea virus; reverse-transcriptase polymerase chain reaction; FTATM cards; blood samples